2012
DOI: 10.1016/j.neuron.2012.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Learning in the Fast Lane: New Insights into Neuroplasticity

Abstract: The timescale of structural remodeling that accompanies functional neuroplasticity is largely unknown. Although structural remodeling of human brain tissue is known to occur following long-term (weeks) acquisition of a new skill, little is known as to what happens structurally when the brain needs to adopt new sequences of procedural rules or memorize a cascade of events within minutes or hours. Using diffusion tensor imaging (DTI), an MRI-based framework, we examined subjects before and after a spatial learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
438
5
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 451 publications
(504 citation statements)
references
References 39 publications
37
438
5
4
Order By: Relevance
“…The findings also show that we may not yet have reached the lower limit on how much training is necessary to produce such changes, indicating remarkably rapid short-term structural neuroplasticity of the hippocampus. The study provides an important, independent confirmation of the meticulous previous work carried out in a single laboratory (Blumenfeld-Katzir et al, 2011;Sagi et al, 2012;Hofstetter et al, 2013;Tavor et al, 2013). Like the previous work, this study shows that the magnitude of diffusivity changes in hippocampus are significantly related to the behaviorally-measured magnitude of the learning changes.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The findings also show that we may not yet have reached the lower limit on how much training is necessary to produce such changes, indicating remarkably rapid short-term structural neuroplasticity of the hippocampus. The study provides an important, independent confirmation of the meticulous previous work carried out in a single laboratory (Blumenfeld-Katzir et al, 2011;Sagi et al, 2012;Hofstetter et al, 2013;Tavor et al, 2013). Like the previous work, this study shows that the magnitude of diffusivity changes in hippocampus are significantly related to the behaviorally-measured magnitude of the learning changes.…”
Section: Discussionsupporting
confidence: 87%
“…The landmark sorting task was scored by following the general procedure reported by Sagi et al (2012). For each of the eight screenshots in each test, one point was given for each of the other screenshots that it correctly preceded in the participants sorting response.…”
Section: Behavioral Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Additional evidence came from studies showing that teaching adults how to juggle altered grey-matter concentrations in the visual and parietal cortex 55 , a change that occurred in as quickly as seven days 56 , and was accompanied by changes in water diffusion in underlying white matter 57 . Microstructural changes have even been detected using diffusion MRI within two hours of playing a video game 58 . Further work by multiple groups has shown that MRI can detect brain plasticity in motor coordination tasks 59 and musical training 60 amongst others.…”
Section: Applications Of Structural Mrimentioning
confidence: 99%
“…Intensive training of normal controls for ~6 weeks changes WMM through induction of long-term potentiation (LTP) [131] . Excitingly, a more recent study showed that short-term training for only two hours results in microstructural changes in the brain that can be detected by a general DTI framework [132] . This demonstrates that the dMRI technique is able to recapitulate the evolution of a network within a relatively short time-scale.…”
Section: Future Directions Of Dmri For Brainnetomementioning
confidence: 99%